Efficacy of a Hybrid Toothbrush versus Comparative Manual Toothbrush for Plaque Removal – Randomized In-Use Study - Favrel S; Urbaniak A; Chabowska I; Sirvent A; Gatignol JP (Clinical, Cosmetic and Investigational Dentistry, 2020)
Stéphanie Favrel,1 Anna Urbaniak,2 Izabela Chabowska,3 Anne Sirvent,4 Jean-Philippe Gatignol5 1Innovation Unit, Clinical Department, Pierre Fabre Consumer Health Care, Castres, France; 2Dental Clinic, Gdansk, Poland; 3Dermscan Poland, Gdansk, Poland; 4Eurofins Dermscan, Villeurbanne, France; 5Innovation Unit, Medical Department, Pierre Fabre Consumer Health Care, Castres, FranceCorrespondence: Jean-Philippe GatignolInnovation Unit, Medical Department, Pierre Fabre Consumer Health Care, Péraudel, 17, Avenue Jean Moulin, Castres 81106, FranceTel +33 563 516 804Email jean.philippe.gatignol@pierre-fabre.comPurpose: An innovative hybrid toothbrush was designed to function either in manual sonic mode or combined mode (manual and sonic). The primary objective was to assess the efficacy of a new hybrid powered toothbrush (PTB) used in combined mode versus a comparative manual toothbrush (MTB) for plaque removal, after 14 days of twice-daily use under normal conditions. The secondary objectives were to evaluate the gingival state, to evaluate the tolerance of the hybrid PTB and to evaluate its acceptability.Materials and Methods: This study was a monocentric, block-randomized, dual treatment, parallel group, and examiner-blinded trial with before and after evaluation. It was conducted on two groups of 55 subjects presenting a visible plaque accumulation (score ≥ 2 as measured by the Turesky Modification of the Quigley-Hein Plaque Index (TMQHPI)). On Day 1/Day 8/Day 15, the same investigator conducted blind clinical examinations on each subject and evaluated TMQHPI and Papillary Bleeding Score (PBS). On Day 1, the subjects received either the hybrid PTB or the comparative MTB and used it twice daily under normal conditions of use.Results: The hybrid PTB used in its combined mode eliminates dental plaque more efficiently than the comparative MTB, especially in difficult-to-access areas such as posterior and interproximal dental surfaces, while remaining gentle on the gingivae. The PBS was significantly lower with the hybrid toothbrush compared with the reference manual one.Conclusion: The new device confirmed previous findings and should improve oral hygiene following the manufacturer’s instructions. Moreover, the specific design of the toothbrush means that it can be used according to the oral environment conditions and personal feeling.Keywords: powered toothbrush, sonic toothbrush, dental plaque, oral health